2011
DOI: 10.1007/s00267-011-9639-y
|View full text |Cite
|
Sign up to set email alerts
|

Combining Conservation Value, Vulnerability, and Effectiveness of Mitigation Actions in Spatial Conservation Decisions: An Application to Coastal Oil Spill Combating

Abstract: Increasing oil transportation and severe oil accidents in the past have led to the development of various sensitivity maps in different countries all over the world. Often, however, the areas presented on the maps are far too large to be safeguarded with the available oil combating equipment and prioritization is required to decide which areas must be safeguarded. While oil booms can be applied to safeguard populations from a drifting oil slick, decision making on the spatial allocation of oil combating capaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 22 publications
0
28
0
1
Order By: Relevance
“…(3) Expressing the potential gains and losses in terms of biodiversity. In the present example, the ecosystem components and areas to be taken into consideration could include the potential mortality of bird or seal populations, the amount of oiled shoreline and the affected flora and fauna, fish populations that may be affected by dispersed oil, and specific endangered species or populations that may be affected by the stranded oil (e.g., Ihaksi et al, 2011;Lecklin et al, 2011). Choosing valuation approaches to identify the best management decisions depends on the type of biodiversity to be analysed and the abundance and quality of available data.…”
Section: Referencesmentioning
confidence: 99%
“…(3) Expressing the potential gains and losses in terms of biodiversity. In the present example, the ecosystem components and areas to be taken into consideration could include the potential mortality of bird or seal populations, the amount of oiled shoreline and the affected flora and fauna, fish populations that may be affected by dispersed oil, and specific endangered species or populations that may be affected by the stranded oil (e.g., Ihaksi et al, 2011;Lecklin et al, 2011). Choosing valuation approaches to identify the best management decisions depends on the type of biodiversity to be analysed and the abundance and quality of available data.…”
Section: Referencesmentioning
confidence: 99%
“…The key idea in risk assessment is to select the most convenient assumptions and methodologies that will put forth the most likely outcomes so that the decision-makers can judge the risks. In the study of Ihaksi et al (2011), the areas presented on the maps are far too large to be safeguarded with the available oil combating equipment and prioritization is required to decide on the areas that must be safeguarded. Therefore, an index-based method to be used in the Gulf of Finland (Baltic Sea) for operational oil combating to make decisions concerning which populations of natural organisms that should primarily be safeguarded from a floating oil slick with oil booms is developed and applied.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, Yu et al (2012) showed how the integration of traditional and HTS methods made for a rapid way to assess arthropod biodiversity, both taxonomic and phylogenetic. The ability to deploy high precision methods in a short amount of time will become instrumental to react rapidly to environmental emergencies, some of which made the news over the last 2 years (Campagna et al 2011; Ihaksi et al 2011). In the case of the Deepwater Horizon oil spill, resident petroleum degrading bacteria were accounted for in the strategies implemented to deal with the crisis, stressing why a good understanding of the taxonomic and functional composition of the community can be crucial.…”
Section: Discussionmentioning
confidence: 99%